Mapping A Decade Of Financial Technology Landscape : Open Knowledge Maps - Alien Akmalia (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The study of financial technology has become one of the most interesting studies for researchers in recent years. The purpose of this paper is to present the development of research on financial technology over the last 10 years. This study analyzed 85 papers in terms of financial technology using the Open Knowledge Maps (OKM) application. The data source was obtained from the metadata of scientific journals from 2013 – 2022. Based on the results of analysis using open knowledge maps shows that there are 11 research clusters on financial technology. There are three key dimensions of the result analysis are highlighted: (1) an exhaustive overview and descriptive information for the complete document set sourced from BASE-indexed articles, (2) data on article categorization into relevant clusters along with corresponding document counts, and (3) areas related to financial technology that present substantial opportunities for future research agenda. The results indicate that there is considerable interest in studying financial technology in terms of demography and linking it to corporate innovation. Numerous underexplored research opportunities exist in the fintech domain, including themes such as human capital, innovation capability, sharia financial technology, peer-to-peer lending, and financial literacy. This study contributes to both practical and academic areas by (1) it can guide decision-making processes related to the company's use of financial technology, (2) this research can serve as a foundation for identifying research gaps, and as a reference source for future studies in the field of financial technology.